Fast oxygen exchange and diffusion kinetics of grain boundaries in Sr-doped LaMnO3 thin films. Issue 12 (28th March 2015) - Navickas, Edvinas; Huber, Tobias M.; Chen, Yan; Hetaba, Walid; Holzlechner, Gerald; Rupp, Ghislain; Stöger-Pollach, Michael; Friedbacher, Gernot; Hutter, Herbert; Yildiz, Bilge; Fleig, Jürgen
<x xml:space="preserve">Abstract</x> Isotope exchange depth profile measurements were performed on columnar/epitaxial LSM thin films with varied microstructure. These uncover the importance of grain boundaries for oxygen reduction reaction and oxide ion diffusion.